1994
DOI: 10.1046/j.1365-2648.1994.20061085.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of nursing care: an emerging theory of interpersonal competence

Abstract: Nurse-patient interactions were examined to identify elements of interpersonal competence among nurses from the perspective of patients. Forty patients and 12 nurses participated in this qualitative study at a private acute care hospital. Two-hundred and forty-five observations were completed. Open-ended questions were utilized in 85 audio-taped semi-structured interviews. Data collection and analysis occurred simultaneously using the constant comparative method. Four major processes emerged from the data to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 37 publications
3
131
0
6
Order By: Relevance
“…Communication skill includes an extensive repertoire of communication strategies, interpersonal competence (Fosbinder 1994), the ability to personalize the approach to the clients, meaning rate of speech, connecting to the clients' life world, tone of voice, and using shared language (Kaakinen et al 2001). Other concepts subsumed under communication skill were trust, knowledge, caring, respect, and courtesy (Breeze and Repper 1998).…”
Section: Predictors and Influencing Factorsmentioning
confidence: 99%
“…Communication skill includes an extensive repertoire of communication strategies, interpersonal competence (Fosbinder 1994), the ability to personalize the approach to the clients, meaning rate of speech, connecting to the clients' life world, tone of voice, and using shared language (Kaakinen et al 2001). Other concepts subsumed under communication skill were trust, knowledge, caring, respect, and courtesy (Breeze and Repper 1998).…”
Section: Predictors and Influencing Factorsmentioning
confidence: 99%
“…20 The 4 major subthemes of interpersonal skills were translating, getting to know you, establishing trust, and going the extra mile.…”
Section: Patients' Perceptions Of Nurses' Skillmentioning
confidence: 99%
“…A review of the literature by Scandinavian researchers 19 indicated that patients' satisfaction with nursing care is influenced by the nurses' technical competence, as well as by 13 Curtis et al 14 Murray-Gracia et al 15 Tamblyn et al 16 Laidlaw et al 17 Frostholm et al 18 Johansson et al 19 Fosbinder 20 Thorsteinsson 21 Baldursdottir and Jonsdottir 22 Radwin 23 Radwin et al 24 Cescutti-Butler and Galvin 25 Kralik et al …”
Section: Literature Reviewmentioning
confidence: 99%
“…These results are gratifying, as a correct and respectful reception assumes that the staff has sufficient understanding of the patient's situation and knowledge of their problem and also a humanitarian approach. The patient's perception of the quality of the care given depends a great deal on the person-to-person interplay between patient and staff and this has significant effects on whether the patient is satisfied with the care (Fosbinder 1994). In 1969, Kennedy (1969) suggested that it was difficult for patients to express or admit their feelings and none of the patients had talked to a nurse about the cancellations (Kennedy 1969).…”
Section: Perceptions Of Receptionmentioning
confidence: 99%